Effect of storage condition and storage duration on grain quality of wheat - Devkota Wasti, Mina Kumari; Ouyachchou, Mariam; Bagger, Asmae; Aloui, Khawla (International Center for Agricultural Research in the Dry Areas, 2024)
The storage conditions and duration of harvested grain storage may have a significant impact on the concentration of essential nutrients like iron, zinc, and protein in wheat. Poor storage practices, especially in environments with high humidity and temperature, can lead to nutrient degradation and loss of grain quality over time. The objective of this study was to understand if the storage duration and conditions of the storage affects nutritional concentration (zinc, iron and protein) in wheat compared to sample analysed shortly after harvest. The study was implemented for wheat grain in ICARDA quality laboratory, Rabat, Morocco in 2023/24. This study considered two major factors (i) grain storage duration (6 treatments, i.e., immediately after harvest, and an interval of 30, 60, 120, 180, and 360 days after harvest) and (ii) three different storage environments, i.e., room temperature, stored in refrigerator (4oC), and in Freezer (-20oC). The study found that there was no significant effect of storage duration and storage temperature on the concentration of iron, zinc in bread wheat grains. This suggests that if samples may not be possible to process for analyses immediately after harvesting it can be safely stored and analyzed in the convenient time within a year (as the study covers up to 360 days) without affecting these nutrient levels. However, grain protein content was slight reduction after 12 months of storage, i.e., grain protein was reduced by 0.87 (by 5.92%) when stored at room temperature, by 0.97 (6.6%) when stored at 4oC (at refrigerator and reduce by 1.07 (7.28%) when stored at freezer (-200C) compared to the grain protein obtained immediately after harvest (14.7%).